2012
DOI: 10.1186/1471-2164-13-608
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mapping in intraspecific populations uncovers a high degree of macrosynteny between A- and B-genome diploid species of peanut

Abstract: BackgroundCultivated peanut or groundnut (Arachis hypogaea L.) is an important oilseed crop with an allotetraploid genome (AABB, 2n = 4x = 40). Both the low level of genetic variation within the cultivated gene pool and its polyploid nature limit the utilization of molecular markers to explore genome structure and facilitate genetic improvement. Nevertheless, a wealth of genetic diversity exists in diploid Arachis species (2n = 2x = 20), which represent a valuable gene pool for cultivated peanut improvement. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…Simpson, and A. correntina (Burkart) Krapov. Multiple translocations have been observed in A. duranensis and A. batizocoi (Stalker et al, 1991aGuo et al, 2012), which indicates that species are continuing to evolve. The chromosomes of B-genome species are karyologically more diverse than those with an A genome (Fernandez and Krapovickas, 1994;Seijo et al, 2004).…”
Section: Section Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Simpson, and A. correntina (Burkart) Krapov. Multiple translocations have been observed in A. duranensis and A. batizocoi (Stalker et al, 1991aGuo et al, 2012), which indicates that species are continuing to evolve. The chromosomes of B-genome species are karyologically more diverse than those with an A genome (Fernandez and Krapovickas, 1994;Seijo et al, 2004).…”
Section: Section Classificationmentioning
confidence: 99%
“…By crossing two accessions of A. batizocoi, a denser map was developed by Guo et al (2012). Fiftyone common markers were present between the A and B genomes, which indicated synteny between the two genomes.…”
Section: Molecular Technologiesmentioning
confidence: 99%
“…Recently, intraspecific maps for A-genome diploid ( A. duranensis ) and B-genome diploid ( Arachi batizocoi ) have been developed with 1724 and 449 marker loci, respectively, including single nucleotide polymorphisms and expressed sequence tag-simple sequence repeats (EST-SSRs) markers. 21,22 …”
Section: Introductionmentioning
confidence: 99%
“…Analyses of species outside section Arachis have been infrequent. Stalker (1985) reported that the two diploid section Erectoides species A. rigonii 3 A. paraguariensis hybrids had many univalents and Krapovickas and Gregory (1994) (Lu and Pickersgill, 1993;Stalker et al, 1994), seed storage proteins (Singh et al, 1991;Bianchi-Hall et al, 1993;Liang et al, 2006), Restriction Fragment Length Polymorphisms (RFLPs) Paik-Ro et al, 1992), Amplified Fragment Length Polymorphisms (AFLPs) (Milla-Lewis et al, 2005b); Simple Sequence Repeats (SSRs) (Hopkins et al, 1999;He et al, 2005;Hong et al, 2010;Guo et al, 2012;Nagy et al, 2012). Randomly Amplified Polymorphic DNA (RAPDS) (Halward et al, 1992;Lanham et al, 1992;Hilu and Stalker, 1995), and in situ hybridization (Raina and Mukai, 1999;Seijo et al, 2004).…”
Section: Cytology and Evolution Of Arachismentioning
confidence: 99%
“…Fifty-one common markers presented evidence of the high synteny of the B and the A genomes. Guo et al (2012) created a more dense map by crossing two accessions of A. batizocoi. They compared high density A and B genome maps and observed a large amount of synteny between the A and B genomes, but also several inversions and translocations.…”
Section: Genetic Mapsmentioning
confidence: 99%